Unequal uptake of skilled maternal health care services in Ethiopia: cross-sectional data analyses informed by the intersectionality theory - Gebretsadik Shibre (BMJ Open)
Objective To investigate intersectional inequality encompassing socioeconomic, geographical and demographic variables in the use of competent birth and postnatal care services in Ethiopia.Design Data for the study came from a series of the Ethiopia Demographic and Health Surveys. Four major surveys were taken place between 2000 and 2016 and all were included in the study. 9867, 9075, 10 592 and 9915 live births born 5 years preceding the surveys that were attended by skilled health workers in 2000, 2005, 2011 and 2016, respectively, were included in the study. For the postnatal care, only the 2016 survey was used due to sample size issues in the other surveys, and 3843 women having live births 2 years preceding the survey had complete data, allowing for fitting of a model. Since the outcome measures are binary, the logit model was used. Intersectionality was analysed by entering interactions into models.Settings Population-based representative surveys encompassing all areas of Ethiopia.Participants The study subjects are women of reproductive age who had live births 2 years preceding the 2016 survey (for postnatal care) and live births born 5 years preceding the respective surveys (for birth care).Outcome measures The outcome measures are skilled birth and postnatal care services. The postnatal care was for mothers within the first 2 days of giving birth and did not include care for the newborn. Competent maternal health care services are those that are provided by competent health workers: doctors, nurses, midwives and health officers.Results It was observed that women at the crossroads of multiple axes of advantage and disadvantage had better and worse utilisation, respectively. For example, maternal education and residence intersected and predicted coverage of birth care was the highest among secondary schooling women who dwelt in urban settings with the values of 0.255; 95% CI 0.113 to 0.397 in 2000 and 0.589; 95% CI 0.359 to 0.819 in 2016 but was the lowest among non-educated women who lived in rural areas with the values of 0.0236; 95% CI 0.0154 to 0.0317 in 2000 and 0.203; 95% CI 0.177 to 0.229 in 2016.Conclusions It appeared that some women who were at the intersections of multiple axes of disadvantage had the lowest predicted coverage for maternal health care services. The study suggests that targeted interventions be developed for women who are at the intersection of multiple axes of marginalisation and that multiple sectors work in their sphere of resposibility to tackle social determinants of maternity care inequality. Policymakers may consider using intersectionality to inform development of targeted policies and or strategies. Further, future studies include structural drivers in the analysis of intersectionality to gain a better insight into the causes of disparities.